2004
DOI: 10.1128/jcm.42.5.2161-2167.2004
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinvasive Neonatal Group B Streptococcus Has Arisen from a Bovine Ancestor

Abstract: The genetic relatedness and evolutionary relationships between group B streptococcus (GBS) isolates from humans and those from bovines were investigated by phylogenetic analysis of multilocus sequence typing data. The collection of isolates consisted of 111 GBS isolates from cows with mastitis and a diverse global collection of GBS isolates from patients with invasive disease (n ‫؍‬ 83) and carriers (n ‫؍‬ 69). Cluster analysis showed that the majority of the bovine isolates (93%) grouped into one phylogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
134
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(154 citation statements)
references
References 23 publications
16
134
0
4
Order By: Relevance
“…4). Interestingly, these regions were more diverse in CC67 and singletons ST246 and ST260 that are specific to animal strains (15,17). Because these regions are highly conserved only in human isolates, they may be linked to selective advantages in this host that led to the emergence of the dominant clone.…”
Section: Regional Variations In Nucleotide Diversity Identify Putativmentioning
confidence: 99%
See 2 more Smart Citations
“…4). Interestingly, these regions were more diverse in CC67 and singletons ST246 and ST260 that are specific to animal strains (15,17). Because these regions are highly conserved only in human isolates, they may be linked to selective advantages in this host that led to the emergence of the dominant clone.…”
Section: Regional Variations In Nucleotide Diversity Identify Putativmentioning
confidence: 99%
“…Several studies (15)(16)(17) have suggested a role of recombinational replacements in the genome evolution of S. agalactiae, although such exchanges never have been reported under laboratory conditions. To test whether chromosomal fragments could be transferred and exchanged between different S. agalactiae isolates, we assessed the transfer of an erythromycin marker (Erm R ) inserted at 30 different locations (I-1 to I-30) in the chromosome of strain NEM316 belonging to CC23.…”
Section: Demonstration Of Large Chromosomal Exchanges Under Laboratorymentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers believe that GBS serotype does not correlate with evolutionary relationships. Strains of different serotypes and sequence types often share more genes than strains of the same serotype and contain carried and invasive strains, traits suggestive of opportunistic pathogenicity (9,11,12).…”
Section: S Treptococcus Agalactiae Group B Streptococcus (Gbs)mentioning
confidence: 99%
“…Acquisition of bovine GBS by humans has been proposed as 1 plausible explanation (9). Human and bovine GBS isolates have been considered genetically distinct populations (10) and as related populations arising from a common ancestor, presumably bovine (1,9).…”
Section: S Treptococcus Agalactiae Group B Streptococcus (Gbs)mentioning
confidence: 99%